Partnering with community-based organizations to improve equitable access to depression care for underserved older adults in the U.S.: Qualitative formative research - Steinman, Lesley E.; Parrish, Amanda T.; Kohn, Marlana J.; Wu, Sherry; Hara-Hubbard, KeliAnne K.; Brown, Lori; Imam, Syed; Baquero, Barbara; Hannon, Peggy A.; Snowden, Mark B. (Frontiers in Public Health, 2023)
Background: Embedding evidenced-based programs (EBPs) like PEARLS outside clinical settings can reduce inequities in access to depression care. Trusted community-based organizations (CBOs) reach older adults who are underserved; yet PEARLS adoption has been limited. Implementation science aims to close this know-do gap-a more intentional focus on equity is needed to engage CBOs. We partnered with CBOs to better understand their resources and needs to design equitable dissemination and implementation (D&I) strategies to support PEARLS adoption. Methods: We conducted 39 interviews with 24 current and potential adopter organizations and other partners (Feb-Sept 2020). CBOs were purposively sampled for region, type, and priority older populations experiencing poverty (communities of color, linguistically diverse, rural). Using a social marketing framework, we explored barriers, benefits and process for PEARLS adoption; CBO capacities and needs; PEARLS acceptability and adaptations; and preferred communication channels. During COVID-19, interviews addressed remote delivery and changes in priorities. We thematic analyzed transcripts using the rapid framework method to describe the needs and priorities of older adults who are underserved and CBOs that engage them, and strategies, collaborations, and adaptations to integrate depression care in these contexts. Results: During COVID-19, older adults relied on CBO support for basic needs like food and housing. Isolation and depression were also urgent issues within communities, yet stigma remained for depression and depression care. CBOs wanted EBPs with cultural flexibility, stable funding, accessible training, staff investment, and fit with staff and community needs and priorities. Findings guided new dissemination strategies to better communicate how PEARLS is appropriate for organizations that engage older adults who are underserved, including what components are core and what are adaptable to better align with organizations and communities. New implementation strategies support organizational capacity-building through training, technical assistance, and matchmaking for funding and clinical support. Discussion: Findings support CBOs as appropriate depression care providers for older adults who are underserved, and suggest changes to communications and resources to better fit EBPs with resources and needs of organizations and older adults. We are currently partnering with California and Washington organizations to evaluate whether and how these D&I strategies increase equitable access to PEARLS.